ANALISIS IMPLEMENTASI PENGELOLAAN TRANSAKSI NON TUNAI TERHADAP GOOD GOVERNANCE PADA PEMERINTAH KOTA METRO - Habiburrahman Habiburrahman; Herry Soedarsa Goenawan Soedarsa; Winarni Winarni (Jurnal Manajemen dan Bisnis (JMB), 2021)
Abstract The Metro City Government began implementing a non-cash transaction system in early 2017 in accordance with the Metro Mayor's Instruction Number 3 of 2017 concerning the Implementation of Non-Cash Transactions within the Metro City Government in realizing technology-based good governance For the sake of creating accountability, transparency, effectiveness and budget efficiency in government. The method of data collection in this study was through observation, interviews, questionnaires and documentation and qualitative analysis. The results showed that the hypothesis: "Non-cash transactions have a significant effect on good governance in Metro City" is accepted. Whereas the procedure for implementing non-cash transactions in the implementation of government spending at the Metro City Government has been implemented in stages based on the Circular of the Minister of Home Affairs No. realizing the principles of good governance, namely the principles of accountability, transparency, effectiveness and efficiency. In addition, it is related to the principle of transparency in the implementation of local government spending, every transaction becomes real time. The track record of transactions and all transactions can be easily traced and monitored by looking at the bank statement. While on the principle of effectiveness and efficiency, this non-cash transaction can be right on target, effective and timely Keywords: Non-Cash Transactions, Good Governance